1983
DOI: 10.2135/cropsci1983.0011183x002300010032x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in Senescing Soybean Leaves of Similar Plant Ontogeny1

Abstract: Delaying the onset or reducing the rate of leaf senescence may be one means of increasing crop productivity. But before senescence can be controlled, it must first be characterized. We compared the onset of leaf senescence, defined as the time at which apparent photosynthesis began to decline irreversibly, with ribulose‐l,5‐bisphosphate carboxylase (RuBPCase) activity, chlorophyll content, total protein content, leaf diffusive resistance, and dark respiration in outdoorgrown soybean [Glycine max (L.) Merr. ‘Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Most closely and consistently associated with this decline is the loss of RuBP carboxylase protein and activity (1 1, 14, 15, 20, 21). Uncoupled electron transport activity (5,8) and Chl content (14,15,21) also diminish during senescence, but the onset and/or rate of decline may or may not be coupled with the decline in photosynthetic rate. Two hypotheses have been advanced to explain the loss of chloroplast composition and function.…”
mentioning
confidence: 99%
“…Most closely and consistently associated with this decline is the loss of RuBP carboxylase protein and activity (1 1, 14, 15, 20, 21). Uncoupled electron transport activity (5,8) and Chl content (14,15,21) also diminish during senescence, but the onset and/or rate of decline may or may not be coupled with the decline in photosynthetic rate. Two hypotheses have been advanced to explain the loss of chloroplast composition and function.…”
mentioning
confidence: 99%
“…Ontogenic and genotypic changes of leaf photosynthetic rate in soybean (Glycine max L. Merrill) have been studied, and the results indicate that photosynthetic rate is related to physiological traits such as Chl content, soluble protein content, and Rubisco2 activity of soybean leaves (2,5,9,12). Recent studies (3) have further shown that genotypic differences in leaf photosynthetic rate of soybean were mainly related to differences in chloroplast number per unit leaf area.…”
mentioning
confidence: 99%
“…Others have also found that PRO (Mondai et al, 1978;Secor et al, 1983) or CHL (Wittenbach, 1983) may decline later in the senescence process than photosynthesis. However, losses of RuBPCase usually coincide with decline in photosynthesis (Mondai et al, 1978;Wittenbach, 1983;Secor et al, 1983).…”
Section: Cultivar Effectsmentioning
confidence: 96%
“…The filter paper and cell residue was quantitatively Ribulose 1.5-bisphosphate carboxylase Also, on the second day after TPs sampling, the remain ing discs that had been frozen in liquid N were ground in 5 mL of ice-cold, grinding buffer (Secor et al,, 1983) with a small mortar and pestle. The extract was centrifuged at 4200 X g for 20 minutes.…”
Section: Chlorophyll and Soluble Proteinmentioning
confidence: 99%
See 1 more Smart Citation